Age affects sleep microstructure more than sleep macrostructure. (17th January 2017) - Schwarz, Johanna F. A.; Åkerstedt, Torbjörn; Lindberg, Eva; Gruber, Georg; Fischer, Håkan; Theorell‐Haglöw, Jenny
Summary: It is well known that the quantity and quality of physiological sleep changes across age. However, so far the effect of age on sleep microstructure has been mostly addressed in small samples. The current study examines the effect of age on several measures of sleep macro‐ and microstructure in 211 women (22–71 years old) of the 'Sleep and Health in Women' study for whom ambulatory polysomnography was registered. Older age was associated with significantly lower fast spindle (effect size f 2  = 0.32) and K‐complex density ( f 2  = 0.19) during N2 sleep, as well as slow‐wave activity (log) in N3 sleep ( f 2  = 0.21). Moreover, total sleep time ( f 2  = 0.10), N3 sleep (min) ( f 2  = 0.10), rapid eye movement sleep (min) ( f 2  = 0.11) and sigma (log) ( f 2  = 0.05) and slow‐wave activity (log) during non‐rapid eye movement sleep ( f 2  = 0.09) were reduced, and N1 sleep ( f 2  = 0.03) was increased in older age. No significant effects of age were observed on slow spindle density, rapid eye movement density and beta power (log) during non‐rapid eye movement sleep. In conclusion, effect sizes indicate that traditional sleep stage scoring may underestimate age‐related changes in sleep.